(untitled) (ARQUISUR Revista, 2020)
The article analyzes the construction of rental housing in Mar del Plata, one of the most important summer vacation destinations of Argentina. Based on urban history the article focuses on regulations and the most important architectural styles which evidenced the functionality of the apartments. These apartment buildings changed the architectural landscape of Mar del Plata as well as tourist lodging options. They also contributed to the profiling of Mar del Plata as a middle-class tourist city, leaving behind the restrictive offer to elites which charachterized the former period.